Aging‐associated changes in immunological parameters: Implications for COVID‐19 immune response in the elderly - Maha Gasmi; Mahdi Hejazi; Antonella Muscella; Santo Marsigliante; Aastha Sharma (Physiological Reports)
Abstract Aging has a profound impact on the immune system, leading to a gradual decline in its function and increased systemic inflammation, collectively known as immunosenescence and inflammaging. These changes make older adults more susceptible to infections, including COVID‐19, and contribute to worse clinical outcomes, such as higher morbidity and mortality rates. This review explores immunological changes associated with aging, including impaired innate immune responses, reduced T‐ and B‐cell function, and altered cytokine profiles. A comprehensive literature search identified relevant studies on the topic, and inclusion criteria focused on studies addressing age‐related immune changes and their impact on responses to COVID‐19. The findings underscore the need for targeted healthcare strategies to mitigate the negative effects of aging on immunity and improve immune resilience, and ultimately clinical outcomes and quality of life for this vulnerable population.